Frailty in Community-Dwelling Older People in Abu Dhabi, United Arab Emirates: A Cross-Sectional Study - Al-Kuwaiti, Saleha Jaber; Aziz, Faisal; Blair, Iain (Frontiers in Public Health, 2015)
Background Frailty describes the ageing-associated loss of physiological and psychological reserves leading to an increased risk of adverse health outcomes. Many developed countries view frailty as a major priority for their health and social care systems. Less is known about frailty in less-developed countries. The purpose of this study was to determine the prevalence of frailty in a sample of community dwelling older people in the United Arab Emirates. Methods This was a cross sectional study of community dwelling Emirati adults aged 55 years and older (n=160) in Abu Dhabi, United Arab Emirates. Data was collected at interview by questionnaire and physical measurements. Frailty was defined according to the criteria of the Fried Frailty Index. The prevalence of frailty and its association with selected independent variables was assessed. Results The overall prevalence of frailty (95% CI) was 47% (39-55). Higher levels of frailty were seen in older age groups, women, those who were non-married, those with recent hospital admission, those with co-morbid conditions, those on more than five medications and those with lower forced expiratory volume and mini-mental state examination score. After adjustment in a multiple logistic regression model only age and gender were found to be independently associated with frailty. Conclusion A high prevalence of frailty was found amongst older Emiratis. Given that frailty is associated with adverse health outcomes and can be a means of identifying opportunities for intervention in clinical practice and health policy, further attention and consideration within professional and public health policy circles is needed.